Turkey as a U.S. Security Partner - Larrabee, F. Stephen (RAND Corporation, 2008)
Strains in U.S.-Turkish have grown since the end of the Cold War. Divergences have been particularly visible in policy toward the Middle East. As a result, Turkey is likely to be an increasingly difficult and less predictable partner in the future.